Penerapan Lesson Study untuk Meningkatkan Kemampuan Dasar Mengajar Mahasiswa Pendidikan Biologi Universitas Pasir Pengaraian - Lestari, Rena; Afifah, Nurul (Indonesian Biology Teachers, 2018)
Abstract. To improving the teaching ability of preservice teachers must understand eight basic skills of teaching. Lesson study is a model used for teaching guidance for students, because in the model developed collaborative work, collegial and mutual benefit in learning (mutual learning). The purpose of this research is to improve the teaching ability of biology education students of Pasir Pengaraian University by using lesson study model. This research is a classroom action research (PTK). The data source of this research is the sixth semester of Biology education program of Teacher Training and Education Faculty of Pasir Pengaraian University. Data collected by observation sheet of basic teaching skill assessment. The result of the research shows the improvement of students teaching ability on the second cycle (from the first cycle 51,78 to 73,86 in the second cycle). Thus it can be concluded that there is improvement of teaching ability of Biology University of Pasir Pengaraian by applying lesson study model.Â Keywords: basic teaching skills, lesson study, microteaching